2017
DOI: 10.1016/j.yjmcc.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated Cl− current is antiarrhythmic by reducing both spatial and temporal heterogeneity of cardiac repolarization

Abstract: The role of Ca2+-activated Cl− current (ICl(Ca)) in cardiac arrhythmias is still controversial. It can generate delayed afterdepolarizations in Ca2+-overloaded cells while in other studies incidence of early afterdepolarization (EAD) was reduced by ICl(Ca). Therefore our goal was to examine the role of ICl(Ca) in spatial and temporal heterogeneity of cardiac repolarization and EAD formation. Experiments were performed on isolated canine cardiomyocytes originating from various regions of the left ventricle; sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Rabbits were first injected with heparin (1000 U/kg) and then anesthetized with isoflurane inhalation (3–5%). After achieving deep anesthesia, a standard enzymatic technique was used to isolate ventricular myocytes at 37°C as previously described [33, 34]. Briefly, hearts were mounted on a Langendorff system and retrogradely perfused for 5 min with an oxygenated solution containing (in mmol/L): NaCl 138, KCl 5.4, CaCl 2 0.05, MgCl 2 1, NaH 2 PO 4 0.33, NaHCO 3 10, HEPES 10, glucose 6, pyruvic acid 2.5; at pH=7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Rabbits were first injected with heparin (1000 U/kg) and then anesthetized with isoflurane inhalation (3–5%). After achieving deep anesthesia, a standard enzymatic technique was used to isolate ventricular myocytes at 37°C as previously described [33, 34]. Briefly, hearts were mounted on a Langendorff system and retrogradely perfused for 5 min with an oxygenated solution containing (in mmol/L): NaCl 138, KCl 5.4, CaCl 2 0.05, MgCl 2 1, NaH 2 PO 4 0.33, NaHCO 3 10, HEPES 10, glucose 6, pyruvic acid 2.5; at pH=7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Single canine and human myocytes were obtained by enzymatic dispersion using the segment perfusion technique, as described previously [27]. Briefly, a wedge-shaped section of the ventricular wall supplied by the left anterior descending coronary artery was cannulated, dissected and perfused with a nominally Ca 2+ -free Joklik solution (Minimum Essential Medium Eagle, Joklik Modification, Sigma-Aldrich Co. St. Louis, MO, USA) for 5 min.…”
Section: Isolation Of Cardiomyocytesmentioning
confidence: 99%
“…Furthermore, a recent study indicated that 9‐phenanthrol can also inhibit the Ca 2+ ‐activated Cl − current conducted by the TMEM16A channel (Burris et al, ). However, this current contributes to phase 1 repolarization, inhibition of which may prolong APD and facilitate the occurrence of EADs (Hegyi et al, ). As a result, it is unlikely that the antiarrhythmic effect of 9‐phenanthrol is due to TMEM16A channel inhibition.…”
Section: Discussionmentioning
confidence: 99%